2016
DOI: 10.1016/j.jos.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and basic research on steroid-induced osteonecrosis of the femoral head in Japan

Abstract: Clinical and basic research has been performed to determine the pathogenesis of steroid-induced ONFH. Low hepatic CYP3A activity has been reported to significantly contribute to the risk of steroid-induced ONFH. Several gene polymorphisms related to steroid metabolism were shown to be associated with the occurrence of ONFH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 42 publications
1
77
0
Order By: Relevance
“…It is believed that long-term use of GCs can lead to hyperlipidemia and fat accumulation in the bone marrow cavity, which increases marrow cavity pressure and increases the risks of fat embolus formation, venous obstruction, and vascular endothelial damage, all of which promote avascular osteonecrosis. 17 Bian et al 18 reported that dexamethasone regulated lipid metabolism-associated microRNAs in osteogenically induced human mesenchymal stem cells. Metabolomics analysis performed on 30 patients with GC-induced ONFH and 30 healthy controls revealed that the abnormal metabolites induced by GCs were primarily in lipid-, glutathione-, nucleotide-, and energy-associated pathways.…”
Section: Hdl-c and Apo-b/apo-a1: Potential Predictive Value Of Lipid mentioning
confidence: 99%
“…It is believed that long-term use of GCs can lead to hyperlipidemia and fat accumulation in the bone marrow cavity, which increases marrow cavity pressure and increases the risks of fat embolus formation, venous obstruction, and vascular endothelial damage, all of which promote avascular osteonecrosis. 17 Bian et al 18 reported that dexamethasone regulated lipid metabolism-associated microRNAs in osteogenically induced human mesenchymal stem cells. Metabolomics analysis performed on 30 patients with GC-induced ONFH and 30 healthy controls revealed that the abnormal metabolites induced by GCs were primarily in lipid-, glutathione-, nucleotide-, and energy-associated pathways.…”
Section: Hdl-c and Apo-b/apo-a1: Potential Predictive Value Of Lipid mentioning
confidence: 99%
“…On the other hand, osteonecrosis of the jaw related with melphalan alone has not been reported, but it is known as a possible complication from corticosteroid therapy, either alone 10) or combined with other drugs 8) in the treatment of various diseases in humans. However, with regard to pharmacophysiology, it was unclear whether zoledronic acid administration contributed to mandibular necrosis in the current case.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The pathogenesis of ONFH in patients with inflammatory diseases treated with corticosteroids remains unclear, although there has reported as factors caused ischemia due to fat emboli in peripheral blood vessels, reduction in arterial flow through the recruitment of increased adipose tissue and/ or an increase in intramedullary pressure [4,5]. On the other hand, ONFH frequently results in osteoarthritis in young patients [6,7], and no effective prevention strategy or effective nonsurgical treatment for ONFH has been established to date.…”
Section: Introductionmentioning
confidence: 99%